The Resilience of Working Mothers with Cerebral Palsy Children - Yulianti, Natalia Ratna; Aeni, Nur; Gayatina, Andri Kenti (Sahabat Publikasi Kuu, 2024)
The limited owned by children with cerebral palsy make them unable to meet their needs and require assistance of others. The cerebral palsy is very dependent on parents especially mother to meet the daily needs and therefore it will affect the mother’s level of stress. The purpose of this study was to identify the resilience of working mother with cerebral palsy children. This research is quantitative research with a descriptive research design. The sampling technique used in this research was total sampling with the inclusion criteria being working mothers who had children with mild to moderate cerebral palsy. The exclusion criteria were working mothers who were sick and working mothers who cancelled the study. The sample used was 50 working mothers with cerebral palsy children. The research results showed that most of the respondents had a moderate level of resilience was 60% (n=30). Further study on the correlation between those factors and working mother’s resilience are highly recommended. It is suggested that school establish some programs to shape working mother’s high resilience.